Mutual Risks of Cutaneous Melanoma and Specific Lymphoid Neoplasms: Second Cancer Occurrence and Survival. (6th April 2018) - Herr, Megan M; Schonfeld, Sara J; Dores, Graça M; Withrow, Diana R; Tucker, Margaret A; Curtis, Rochelle E; Morton, Lindsay M
Abstract: Background: It is unclear whether the established association between cutaneous melanoma (CM) and lymphoid neoplasms (LNs) differs across LN subtypes. This study quantifies risk for developing CM after specific LNs and, conversely, for developing specific LNs after CM, as well as assessing clinical impact. Methods: We identified a cohort of Caucasian adults (age 20–83 years) initially diagnosed with CM or LN, as reported to 17 US population-based cancer registries, 2000–2014. Standardized incidence ratios (SIRs) quantified second cancer risk. We assessed impact of second cancer development on risk of all-cause mortality using Cox regression. Results: Among 151 949 one-or-more-year survivors of first primary LN, second primary CM risk was statistically significantly elevated after chronic lymphocytic leukemia/small lymphocytic lymphoma (SIR = 1.96, 95% confidence interval [CI] = 1.74 to 2.21), follicular lymphoma (SIR = 1.32, 95% CI = 1.09 to 1.58), and plasma cell neoplasms (SIR = 1.33, 95% CI = 1.07 to 1.63). Risks for these same subtypes were statistically significantly elevated among 148 336 survivors of first primary CM (SIR = 1.44, 95% CI = 1.25 to 1.66; SIR = 1.47, 95% CI = 1.21 to 1.77; SIR = 1.25, 95% CI = 1.06 to 1.47; respectively). Risk for CM was statistically significantly elevated after diffuse large B-cell lymphoma (SIR = 1.22, 95% CI = 1.02 to 1.45) and Hodgkin lymphoma (SIR = 1.75, 95% CI = 1.33 to 2.26), but the reciprocal relationship was not observed. There were no statistically significant associations between marginal zone lymphoma and CM. Among survivors of most LN subtypes, CM statistically significantly increased risk of death (hazard ratio [HR] range = 1.52, 95% CI = 1.25 to 1.85, to 2.46, 95% CI = 1.45 to 4.16). Among survivors of CM, LN statistically significantly increased risk of death (HR range = 1.75, 95% CI = 1.15 to 2.65, to 6.28, 95% CI = 5.00 to 7.88), with the highest risks observed for the most aggressive LN subtypes. Conclusions: Heterogeneous associations between CM and specific LN subtypes provide novel insights into the etiology of these malignancies, with the mutual association between CM and certain LN suggesting shared etiology. Development of second primary CM or LN substantially reduces overall survival.